Speaking club as the method of speaking skills improving - Haidei, K.; Orobinska, M. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The article deals with such a form of foreign students’ speaking skills development as a speaking club. Examples of classes and educational activities are represented. The article deals with the problem of modern students’ motivation during foreign languages studies. Creation of the artificial language surrounding is offered as a productive mean of facilitating motivational and educational processes. The article is illustrated with the methods of creation of the artificial language surrounding that may be used at any stage of teaching foreign languages. Conclusions about the advantages and disadvantages of using this type of activity are made. Speaking skills improving is needed in learning foreign language. The difficulty in communication skills developing lies in the fact of students’ stiffness in using language in real life communication. The communicative failure leads to decreasing students’ motivation. The authors state, that one of possible solutions for this problem is immersion in artificially created language surrounding. It is noted that the creation of the artificial language surrounding includes numerous methods. Most of them encourage students to take part in training activities, thereby contributing to speaking skills improving. Methods of artificial language surrounding are represented and described. It is also pointed out that effective forms of training language include acquaintances of language patterns and dipping into communicative situations. The authors offer the way of connecting these forms in such activity as speaking club. It is emphasized that the informal surrounding of speaking club meetings contributes to active students’ involvement to the conversation. The didactic potential of Russian language speaking club is analyzed. The authors conclude, that the speaking club had positive results not only in improving communication skills, but also in increasing of motivation, cognitive interest.